The MarR-Type Regulator MalR Is Involved in Stress-Responsive Cell Envelope Remodeling in Corynebacterium glutamicum - Hünnefeld, Max; Persicke, Marcus; Kalinowski, Jörn; Frunzke, Julia (Frontiers in Microbiology, 2019)
It is the enormous adaptive capacity of microorganisms, which is key to their competitive success in nature, but also challenges antibiotic treatment of human diseases. To deal with a diverse set of stresses, bacteria are able to reprogram gene expression using a wide variety of transcription factors. Here, we focused on the MarR-type regulator MalR conserved in the Corynebacterineae, including the prominent pathogens Corynebacterium diphtheriae and Mycobacterium tuberculosis. In several corynebacterial species, the malR gene forms an operon with a gene encoding a universal stress protein (uspA). Chromatin affinity purification and sequencing (ChAP-Seq) analysis revealed that MalR binds more than 60 target promoters in the C. glutamicum genome as well as in the large cryptic prophage CGP3. Overproduction of MalR caused severe growth defects and an elongated cell morphology. ChAP-Seq data combined with a global transcriptome analysis of the malR overexpression strain emphasized a central role of MalR in cell envelope remodeling in response to environmental stresses. Prominent MalR targets are for example involved in peptidoglycan biosynthesis and synthesis of branched-chain fatty acids. Phenotypic microarrays suggested an altered sensitivity of a ΔmalR mutant towards several β-lactam antibiotics. We furthermore revealed MalR as a repressor of several prophage genes suggesting that MalR may be involved in the control of stress-responsive induction of the large CGP3 element. In conclusion, our results emphasize MalR as a regulator involved in stress-responsive remodeling of the cell envelope of C. glutamicum and suggest a link between cell envelope stress and the control of phage gene expression.